2019
DOI: 10.1002/cctc.201901481
|View full text |Cite
|
Sign up to set email alerts
|

G‐Quadruplex‐Based Photooxidase Driven by Visible Light

Abstract: The G‐quadruplex (G4)/hemin entity has been widely used as a peroxidase‐mimic DNAzyme to catalyze the substrate oxidation with exogenous and concentrated H2O2 as oxidant for developing various devices. Herein, a G4‐based oxidase‐mimic DNAzyme that can be driven by visible light was developed. The oxidant is in situ produced by light irradiation. As a natural photosensitizer, Hypericin (Hyp) alone in solution is inactive because of aggregation. However, the binding with G4 triggers the fluorescence emission and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…A G4 DNA based hybrid photooxidase, as reported by Gao et al, was recently shown to activate by visible light. [72] This photooxidase was built from a parallel G4 DNA and hypericin through an end-stacking interaction, [73] and was activated by a wide range of visible light (from 490 nm to 610 nm) via the singlet oxygen ( 1 O 2 ) pathway to catalyze the substrate oxidation. Since G4 DNA hybrid catalysts are capable of catalyzing a variety of chemical reactions, including enantioselective Michael addition reactions, asymmetric Diels-Alder reactions, and Friedel-Crafts alkylation reactions, [36] their promise should not be overlooked in the future of biochemical applications under unusual conditions.…”
Section: G4 Dnas In the Presence Of Denaturants And Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…A G4 DNA based hybrid photooxidase, as reported by Gao et al, was recently shown to activate by visible light. [72] This photooxidase was built from a parallel G4 DNA and hypericin through an end-stacking interaction, [73] and was activated by a wide range of visible light (from 490 nm to 610 nm) via the singlet oxygen ( 1 O 2 ) pathway to catalyze the substrate oxidation. Since G4 DNA hybrid catalysts are capable of catalyzing a variety of chemical reactions, including enantioselective Michael addition reactions, asymmetric Diels-Alder reactions, and Friedel-Crafts alkylation reactions, [36] their promise should not be overlooked in the future of biochemical applications under unusual conditions.…”
Section: G4 Dnas In the Presence Of Denaturants And Othersmentioning
confidence: 99%
“…A G4 DNA based hybrid photooxidase, as reported by Gao et al., was recently shown to activate by visible light [72] . This photooxidase was built from a parallel G4 DNA and hypericin through an end‐stacking interaction, [73] and was activated by a wide range of visible light (from 490 nm to 610 nm) via the singlet oxygen ( 1 O 2 ) pathway to catalyze the substrate oxidation.…”
Section: G4 Dnas As Peroxidase Mimicking Dnazymes (Pmds)mentioning
confidence: 99%
“…Since communication systems based on broadband sources have many advantages such as has been previously demonstrated in [Kim 2007, Gra 2009, Gra 2010, Kan 2014, Dim 2015, Kar 2015, Chi 2017b, Sen 2019, Gao 2019, Yeh 2019, Zho 2019, they undoubtedly offer a great opportunity for the future of optical communication both for free space and optical fiber communications.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it offers high data rate compared to the conventional RF-based wireless technologies such as Wi-Fi and Bluetooth, thanks to its huge bandwidth [Pis 2012]. Most of the recent studies on VLC consider the LEDs as transmitter, such as [Erg 2015, Gao 2019, Li 2019a, Sin 2019, Zho 2019, Yeh 2019]. However, according to [Erg 2015], there are two main challenges in utilization of LEDs as transmitter, the limited bandwidth (Bandwidth can be extended with complex type of LEDs); and the nonlinearity (nonlinear relationship between current and optical power in LEDs becomes challenging in high data rate applications).…”
Section: List Of Tablesmentioning
confidence: 99%
See 1 more Smart Citation